Rooms for one : a journey through visible and invisible space - Björklund, Linn Hanna Helena, 1985- (2015)
The need for space can be different depending on where you are situated geographically. My life is in two places, Iceland and Sweden. As a result I often find myself in a state of temporary presence or interim between different cities, countries and languages. Central to my research about personal spaces are thoughts regarding scale and how such a space, within human contexts, can be created in the easiest way possible. I have searched for traces of different kinds of spatial creations within for example childish play, contemporary building techniques and rituals of the past. I draw parallels between contemporary artist practices and historical fragments as well as philosophical influences and movies. The material is thematically connected as it describes how people of different ages, from various cultures and times relate to space and their dwellings. I believe that the question of space is not only connected to the spatial structures that we inhabit but also to a sense of psychological boundaries, that in part defines oneself in one’s own environment. The materials that I have collected strive towards the idea that the forming of an identity is also leaving a physical mark in our shared environment. I envision the building of a pillow fort, a “koja”, as a very basic construction of a private space. Maybe this is the closest we can get to visualize and operationalize the human instinct to nest, established as a part of children’s play but having a deeper root in the way we shape identity and model a self-image. In the project Welcome here I created these pillow forts and my own borders for a personal space by crossing others on an already existing map. I cut through the city landscape as well as the borders of people’s homes and workplaces. I found that the personal space is not always visible and can be claimed by other means than material ones. In the exhibition I invited people to continue the journey I had taken. Through sound, text and images the audience could move between nine different locations guided ...